2007
DOI: 10.1007/s11605-007-0155-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcome After Resection for Chronic Pancreatitis in 224 Patients

Abstract: Pancreatic resection leads to adequate pain control in the majority of patients with CP. Long-term outcome does not depend on the type of surgical procedure but is in part influenced by severe preoperative CP and by postoperative surgical complications (regarding pain). A few patients develop procedure-related late complications. Late mortality is high, probably because of the high comorbidity (alcohol, smoking) in many of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
1
10

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(80 citation statements)
references
References 29 publications
5
64
1
10
Order By: Relevance
“…Of the 77 patients whose pancreatic endocrine functions were assessed, 7 had glucose intolerance, 8 had diabetes mellitus preoperatively, 18 (23%) showed diabetes mellitus immediately after pancreatic resection, and another 14 developed ‘delayed’ diabetes mellitus within a median period of 27 months from surgery to onset. Together with other clinical studies, these findings show that patients with chronic pancreatitis have a 25–50% risk of developing diabetes mellitus shortly after distal pancreatectomy [7,10,11]. …”
Section: Incidence Of Diabetes After Pancreatic Resection (Table 1)supporting
confidence: 75%
See 2 more Smart Citations
“…Of the 77 patients whose pancreatic endocrine functions were assessed, 7 had glucose intolerance, 8 had diabetes mellitus preoperatively, 18 (23%) showed diabetes mellitus immediately after pancreatic resection, and another 14 developed ‘delayed’ diabetes mellitus within a median period of 27 months from surgery to onset. Together with other clinical studies, these findings show that patients with chronic pancreatitis have a 25–50% risk of developing diabetes mellitus shortly after distal pancreatectomy [7,10,11]. …”
Section: Incidence Of Diabetes After Pancreatic Resection (Table 1)supporting
confidence: 75%
“…For patients with chronic pancreatitis, the risk of diabetes mellitus shortly after distal pancreatectomy is 25–50% [7,10,11,12], and late-onset diabetes tends to be related to the clinical course of chronic pancreatitis [12]. For patients with normal pancreatic parenchyma and tumorous lesions, the rate of diabetes mellitus is relatively low shortly after distal pancreatectomy.…”
Section: Incidence Of Diabetes After Pancreatic Resection (Table 1)mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Riediger et al [21] reported 87% improvement in pain control of 224 patients as far as 10 years after pancreatic head resection. However, 72% of these patients were back on narcotic medications despite using lower doses.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the success rate of pain control after pancreatectomy seems to depend largely on the definition of "success " [21] . Nonetheless, the most effective and most durable pancreatic surgeries performed for pain control in chronic pancreatitis seem to involve resection of the head of pancreas when compared with denervation or decompression procedures [18][19][20][21] . Our series had a 3 years median duration of follow up raising the question about the durability of the reported rate of 80%.…”
Section: Discussionmentioning
confidence: 99%